English for Specific Purposes: mapping discourse genres in a technical school - Bevilaqua, Raquel; Didoné, Patricia de Teixeira de Oliveira (The ESPecialist, 2022)
The expansion of the Federal Network of Vocational, Scientific, and Technological Education, which comprises many federal institutions aimed at secondary and post-secondary professional education throughout the country, presents a challenge for English language teachers, as they will be required to teach to a wide range of audiences. The lack of familiarity with the different professional areas is often an obstacle, worsened by the lack of teaching materials directed towards the different professional areas. As such, teachers are often faced with the need to produce one’s teaching material, and ESP can contribute by helping the language teacher investigate their students’ literacy needs. As a result, this study presents the findings of a student needs analysis whose aim was to map discourse genres for academic and professional purposes, which could aid in developing both an ESP course design and pedagogical material for four post-secondary technical courses offered by a technical school in Rio Grande do Sul. Data collection drew on unstructured interviews with students and their domain specialists and two semi-structured questionnaires.